Mechanisms of Undersensing by a Noise Detection Algorithm That Utilizes Far‐Field Electrograms With Near‐Field Bandpass Filtering. (19th January 2017) - KONERU, JAYANTHI N.; SWERDLOW, CHARLES D.; PLOUX, SYLVAIN; SHARMA, PARIKSHIT S.; KASZALA, KAROLY; TAN, ALEX Y.; HUIZAR, JOSE F.; VIJAYARAMAN, PUGAZHENDI; KENIGSBERG, DAVID; ELLENBOGEN, KENNETH A.
Noise Detection Algorithm Pitfalls: Background: Implantable cardioverter defibrillators (ICDs) must establish a balance between delivering appropriate shocks for ventricular tachyarrhythmias and withholding inappropriate shocks for lead‐related oversensing ("noise"). To improve the specificity of ICD therapy, manufacturers have developed proprietary algorithms that detect lead noise. The SecureSense TM RV Lead Noise discrimination (St. Jude Medical, St. Paul, MN, USA) algorithm is designed to differentiate oversensing due to lead failure from ventricular tachyarrhythmias and withhold therapies in the presence of sustained lead‐related oversensing. Methods and Results: We report 5 patients in whom appropriate ICD therapy was withheld due to the operation of the SecureSense algorithm and explain the mechanism for inhibition of therapy in each case. Limitations of algorithms designed to increase ICD therapy specificity, especially for the SecureSense algorithm, are analyzed. Conclusion: The SecureSense algorithm can withhold appropriate therapies for ventricular arrhythmias due to design and programming limitations. Electrophysiologists should have a thorough understanding of the SecureSense algorithm before routinely programming it and understand the implications for ventricular arrhythmia misclassification.